Neurofibromatosis 1 French national guidelines based on an extensive literature review since 1966 - Bergqvist, Christina; Servy, Amandine; Valeyrie-Allanore, Laurence; Ferkal, Salah; Combemale, Patrick; Wolkenstein, Pierre (Orphanet journal of rare diseases, 2020)
Neurofibromatosis type 1 is a relatively common genetic disease, with a prevalence ranging between 1/3000 and 1/6000 people worldwide. The disease affects multiple systems with cutaneous, neurologic, and orthopedic as major manifestations which lead to significant morbidity or mortality. Indeed, NF1 patients are at an increased risk of malignancy and have a life expectancy about 10–15 years shorter than the general population. The mainstay of management of NF1 is a patient-centered longitudinal care with age-specific monitoring of clinical manifestations, aiming at the early recognition and symptomatic treatment of complications as they occur. Protocole national de diagnostic et de soins (PNDS) are mandatory French clinical practice guidelines for rare diseases required by the French national plan for rare diseases. Their purpose is to provide health care professionals with guidance regarding the optimal diagnostic and therapeutic management of patients affected with a rare disease; and thus, harmonizing their management nationwide. PNDS are usually developed through a critical literature review and a multidisciplinary expert consensus. The purpose of this article is to present the French guidelines on NF1, making them even more available to the international medical community. We further dwelled on the emerging new evidence that might have therapeutic potential or a strong impact on NF1 management in the coming feature. Given the complexity of the disease, the management of children and adults with NF1 entails the full complement healthcare providers and communication among the various specialties.